Histomorphometric and immunohistochemical study shows that tricalcium silicate cement associated with zirconium oxide or niobium oxide is a promising material in the periodontal tissue repair of rat molars with perforated pulp chamber floors - Barbosa, D. D. [UNESP]; Delfino, M. M. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Tanomaru-Filho, M. [UNESP]; Sasso-Cerri, E. [UNESP]; Silva, G. F.; Cerri, P. S. [UNESP] (Wiley, 2021)
Aim: To evaluate the periodontium response to tricalcium silicate (TCS) with zirconium oxide (ZrO2) or niobium oxide (Nb2O5) used in the sealing of perforated pulp chamber floors in rat maxillary molars. Methodology: In eighty rats, the perforations in right maxillary molars were filled with either TCS + ZrO2, TCS + Nb2O5, White MTA (used as a gold standard material) or no repair material was placed (Sham Group, SG); the left molars of SG, were used as controls (CG). Sections of maxillary fragments following 7, 15, 30 and 60 days were used to evaluate the volume densities of inflammatory cells (VvIC) and fibroblasts (VvFb), width of the periodontal space, amount of collagen, number of osteoclasts and number of IL-6-immunostained cells. The data were subjected to two-way ANOVA followed by Tukey’s test (P ≤ 0.05). Results: At all periods, significant differences in VvIC were not detected among TCS + ZrO2, TCS + Nb2O5 and MTA groups, which had values significantly lower (P < 0.05) than the SG. Significant differences in the number of IL-6-immunolabelled cells were not observed among TCS + ZrO2, TCS + Nb2O5 and MTA groups (P > 0.05) at 15, 30 and 60 days. At 7, 15 and 30 days, the number of osteoclast was significantly greater in TCS + ZrO2, TCS + Nb2O5 and MTA (P < 0.05) than in the CG; no significant difference was detected after 60 days (P > 0.05). The width of the periodontal space and amount of collagen in TCS + ZrO2 and TCS + Nb2O5 groups were similar to the CG at 30 and 60 days while SG specimens had a significant reduction (P < 0.05) in the amount of collagen and significant increase (P < 0.05) in the width of the periodontal space. Conclusions: TCS + ZrO2 and TCS + Nb2O5 were associated with periodontium repair since these materials allowed the reestablishment of periodontal space width and collagen formation when used in the filling of uninfected perforations in the pulp chamber floor of maxillary rat molars. Furthermore, the significant reduction in the periodontal space of TCS + ZrO2 and TCS + Nb2O5 specimens after 60 days confirmed that the experimental materials were associated with a more rapid recovery of the injured tissues than MTA.
Keywords: bone resorption; collagen; immunohistochemistry; inflammatory reaction; interleukin-6; osteoclast